2008
DOI: 10.1029/2007jc004354
|View full text |Cite
|
Sign up to set email alerts
|

Arctic waters and marginal ice zones: 2. An investigation of arctic atmospheric infrared absorption for advanced very high resolution radiometer sea surface temperature estimates

Abstract: [1] The derivation of sea surface temperatures (SST) from satellite radiometric data is well established in temperate latitudes. Water vapor is typically the greatest clear sky absorber of infrared (IR) energy between the emitting surface and spaceborne sensor, necessitating a corrective term for SST calculation. Algorithms developed for advanced very high resolution radiometers (AVHRR) use the difference in brightness temperatures between Channel 4 (10.3 to 11.3 mm) and Channel 5 (11.5 to 12.5 mm), or T45, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…This study exploits the efforts of the Global Ocean Data Assimilation Experiment (GODAE) High Resolution SST Pilot Project to recalibrate and match observations from a succession of seven NOAA polar orbiting satellites. Our brief comparison of this product to in situ surface temperature observations shows the presence of a À0.35 C cool bias in water with temperatures above 4 C, consistent with previous studies by Vincent et al [2008aVincent et al [ , 2008b. Unexpectedly we also find enhanced scatter and a warm bias of up to 1 C in regions of cooler temperatures that are also close to the edges of the sea ice.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This study exploits the efforts of the Global Ocean Data Assimilation Experiment (GODAE) High Resolution SST Pilot Project to recalibrate and match observations from a succession of seven NOAA polar orbiting satellites. Our brief comparison of this product to in situ surface temperature observations shows the presence of a À0.35 C cool bias in water with temperatures above 4 C, consistent with previous studies by Vincent et al [2008aVincent et al [ , 2008b. Unexpectedly we also find enhanced scatter and a warm bias of up to 1 C in regions of cooler temperatures that are also close to the edges of the sea ice.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This technique has also been employed by Vincent et al (2008) for the retrieval of surface temperatures in the polar regions. The atmospheric humidity is much lower in polar regions and use of the window channels (e.g., channel 4 and channel 5 of AVHRR) may not work well because of the lack of correlation of the difference of these channels with water vapor and humidity in these regions.…”
Section: B Avhrr Surface Temperature Time Seriesmentioning
confidence: 99%
“…In addition, studies on SST retrieval have shown that split window algorithms, sometimes, perform poorly in high latitudes. During winter, ice fog and ice clouds, which are difficult to detect, interfere with IR absorption and emission [60]. Therefore, we speculate that misestimating Arctic atmosphere properties (by using atmospheric profiles from lower latitudes with relatively higher temperature and water vapor concentration) could result in the high negative bias observed during the winter.…”
Section: The Bias Towards Clear-sky Observationsmentioning
confidence: 98%